3D printing and additive manufacturing of cereal-based materials: Quality analysis of starch-based systems using a camera-based morphological approach. (July 2020) - Fahmy, Ahmed Raouf; Becker, Thomas; Jekle, Mario
Abstract: Structural control over cereals' crumb matrix is achievable using 3D printing. The manipulation of the cellular structure including void fraction, pore size, geometry, and distribution is achievable by resolving large structures into finite layers. However, investigating the applicability of material extrusion for printing starch and cereal-based systems is of great interest due to the behavior of the thixotropic and pseudoplastic materials during extrusion and their viscoelastic post-printing geometric response. In this study, we use an on-board camera system composed of top- and side-view cameras to characterize the post-printing geometrical attributes of two cereal-based systems, which comprise of wheat flour dough and wheat starch-egg white protein blends. This quantitative method uses image processing techniques to obtain morphological dimensional parameters. Furthermore, the induced defects involving printing delays and under-extrusion are influenced by the material's yielding behavior. Over-extrusion defects are dominant in printing wheat flour dough due to the network formation of gluten which caused the collapse of the uppermost layer. Moreover, the structural collapse behavior for the printing ink systems is obtained concerning the hydration level of the dry components. For the first time, the quality behaviors and dimensional attributes were quantitatively studied using on-board imaging and analysis of 3D printed cereal-based morphologies. Graphical abstract: Unlabelled Image Highlights: A quantitative camera-based morphological approach is proposed for geometry and defects analysis of food 3D printing. Gluten network presence leads to adhesive discrepancies depending on printing and movement directions. Gluten network acts as a structural stabilization element for 3D printing. Liquid rope coiling occurs due to structural collapse of the printed layers. The presented method can be modified and incorporated in online detection systems for closed loop control.